Manajemen Laba oleh Perusahaan Pengakuisisi sebelum Merger dan Akuisisi di Indonesia - Hadri Kusuma; Wigiya Ayu Udiana Sari (Jurnal Akuntansi dan Auditing Indonesia, 2003)
The primary objective of this study is to investigate whether there is any manipulation of accounting earnings through discretionary accrual choices by acquiring firms in the period pre¬ceding the announcement and completion of mergers and acquisitions. The current study hy¬pothesised that the process of merger and acquisition may provide incentives for management of the company to make accounting choices that increase the earnings of the firm. The results in the current study provide evidence that in the years prior to the acquisition, acquiring firms do not manage accounting earnings through discretionary accruals. The result, however, indicates that acquiring firms in Indonesia manipulate accounting earnings through income smoothing.Keywords: mergers and acquisitions, discretionary accruals, earnings management, and income smoothing.